Pelaksanaan Pendaftaran Tanah Sistematis Lengkap di Kota Yogyakarta - Windarti Woliyono, Sri; Hidayat, Beni (Recital Review, 2024)
Legal certainty in terms of legal protection for holders of land rights is the aim of land registration, where proof regarding land rights is explained in the final process of land registration, namely a document and land certificate. To support the implementation of land registration, the government is implementing a complete systematic land registration (PTSL) program which is being carried out for the first time simultaneously for all land registration objects in the territory of the Republic of Indonesia in one village/kelurahan area or other equivalent name which includes the collection of physical data. and juridical data regarding one or several land registration objects for registration purposes. This research aims to identify factors in the implementation of land registration in Yogyakarta City by the National Land Agency of Yogyakarta City as well as obstacles to the implementation of complete systematic land registration. This research is empirical legal research. The research used primary data and secondary data by conducting interviews with employees of the Yogyakarta National Land Agency. The research results stated that the implementation of complete systematic land registration in the City of Yogyakarta carried out by the Yogyakarta National Land Agency went through several stages. The implementation and stages are in accordance with Ministerial Regulation No. 6 of 2018 concerning Systematic Complete Land Registration and Presidential Instruction Number 2 of 2018 concerning the Acceleration of Land Registration. Factors that become obstacles in implementing complete systematic land registration in the City of Yogyakarta include the lack of enthusiasm from the community and socialization of the Yogyakarta City land agency regarding the importance of a certificate of ownership of the land rights they own in the future and there is still a lot of land in the City of Yogyakarta whose owners do not have complete documents and the land is still in dispute.